Eksistensi Ketetapan Majelis Permusyawaratan Rakyat Setelah Perubahan Undang-Undang Dasar Negara RI Tahun 1945 Dalam rangka Penataan Tertib Peraturan Perundang-Undangan di Indonesia - Ferry Edwar (Faculty of Law, Universitas Pekalongan, 2025)
The amendment of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) has resulted in fundamental changes to Indonesia’s constitutional system compared to the pre-amendment period. One of the most significant changes is the transformation of the state's organizational structure from a distribution of power model—where the People’s Consultative Assembly (MPR) functioned as the embodiment of popular sovereignty—toward a separation of powers model based on the principle of checks and balances. This shift is particularly evident in the provisions of Article 1(2) in conjunction with Article 3 of the 1945 Constitution. The redefinition of the MPR’s position, functions, duties, and authorities has legal implications for the status and hierarchy of MPR decrees (TAP MPR) within the national legal system. The reinstatement of certain TAP MPR following the constitutional amendments was formalized through Article I of the Supplementary Provisions of the 1945 Constitution and later reaffirmed in TAP MPR No. I/MPR/2003 concerning the Existence of TAP MPR: Review of the Material and Legal Status of Decrees of the Provisional People's Consultative Assembly and the People's Consultative Assembly from 1960 to 2002. From a positive legal perspective, the existence of TAP MPR is officially recognized as a category of legislation and incorporated into the legal hierarchy. However, from a legislative science perspective, the legal norm established in Article I of the Supplementary Provisions of the 1945 Constitution is problematic and unconstitutional, as it contradicts the 1945 Constitution itself. This issue has broader implications for the validity of TAP MPR as part of the national legal framework and necessitates a systematic approach to ensuring a more coherent and orderly legislative system in the future. This study seeks to address the following research questions: Is the existence of TAP MPR, as currently in effect, constitutionally valid? What legal measures should be taken regarding the continued validity of TAP MPR in the effort to establish a coherent legislative system in Indonesia? This research adopts a normative legal approach utilizing doctrinal normology, with historical and juridical-analytical methodologies. The data used in this study consist of secondary data sources, including primary legal materials, secondary legal materials, and tertiary legal materials. The key findings of this study are as follows: The Legal Status of TAP MPR: From a juridical perspective, the existence of TAP MPR/MPRS is based on Article I of the Supplementary Provisions of the 1945 Constitution. However, from a legislative science perspective, the formulation of this legal norm is unconstitutional, as it contradicts Article 1(2) in conjunction with Article 3 of the 1945 Constitution. Given that the legal basis for recognizing TAP MPR is unconstitutional, its regulation in lower-ranking legislation—namely, TAP MPR No. I/MPR/2003 and Law No. 12 of 2011—is also unconstitutional by extension (mutatis mutandis). The unconstitutional nature of Article I of the Supplementary Provisions has, in effect, allowed the MPR to engage in legal maneuvering, resulting in the issuance of TAP MPR No. I/MPR/2003. Consequently, TAP MPR No. I/MPR/2003 itself must also be deemed unconstitutional. Furthermore, the existence of TAP MPR as a component of positive law has been formalized in Law No. 12 of 2011 on the Formation of Laws and Regulations, which recognizes TAP MPR as a category of legislation and includes it within the legal hierarchy. However, the juridical recognition of TAP MPR within this law is also unconstitutional, as it is derived from an unconstitutional legal foundation. Legal Measures for Legislative Reform in Indonesia: First, the MPR should amend the 1945 Constitution by removing Article I of the Supplementary Provisions to eliminate the unconstitutional basis for TAP MPR. Second, the MPR should conduct a legislative review of TAP MPR No. I/MPR/2003 by issuing an MPR decision to revoke and declare it null and void. This can be further reinforced through legislative review and judicial review (i.e., a constitutional challenge) against Law No. 12 of 2011 to ensure its alignment with the constitutional framework. By implementing these legal measures, Indonesia can establish a more structured and constitutionally sound legislative system, ensuring consistency with the principles enshrined in the 1945 Constitution.